1986
DOI: 10.1017/s0043174500067096
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Rooting of Zoysiagrass (Zoysia japonica) as Affected by Preemergence Herbicides

Abstract: Preemergence applications of herbicides were evaluated for their effect on establishment of zoysiagrass (Zoysia japonicaSteud.) with competition from either smooth crabgrass [Digitaria ischaemum(Schreb.) Muhl. # DIGIS] or goosegrass [Eleusine indica(L.) Gaertn. # ELEIN]. When ‘Meyer’ and ‘Belair’ zoysiagrass plugs were grown in sand and treated in the greenhouse, none of the herbicides reduced root weight or length. When plugs were grown in a Sassafrass sandy loam, bensulide {O,O-bis(1-methylethyl)-S-[2-[(phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Application of oxyfluorfen and oxadiazon effectively controlled weeds and increased shoot dry weights and bulb yields in garlic (Qasem, 1996) and shoot fresh and dry weight yields in marjoram (Qasem and Foy, 2006). In zoysiagrass (Zoysia japonica), applications of oxadiazon enhanced sprig establishment due to reduced competition with weeds (Carroll et al, 1996;Fagerness et al, 2002;Fry et al, 1986). Fry et al (1986) observed an increase in stolon production of zoysiagrass treated with oxadiazon due to decreased smooth crabgrass competition.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Application of oxyfluorfen and oxadiazon effectively controlled weeds and increased shoot dry weights and bulb yields in garlic (Qasem, 1996) and shoot fresh and dry weight yields in marjoram (Qasem and Foy, 2006). In zoysiagrass (Zoysia japonica), applications of oxadiazon enhanced sprig establishment due to reduced competition with weeds (Carroll et al, 1996;Fagerness et al, 2002;Fry et al, 1986). Fry et al (1986) observed an increase in stolon production of zoysiagrass treated with oxadiazon due to decreased smooth crabgrass competition.…”
Section: Resultsmentioning
confidence: 88%
“…In zoysiagrass (Zoysia japonica), applications of oxadiazon enhanced sprig establishment due to reduced competition with weeds (Carroll et al, 1996;Fagerness et al, 2002;Fry et al, 1986). Fry et al (1986) observed an increase in stolon production of zoysiagrass treated with oxadiazon due to decreased smooth crabgrass competition.…”
Section: Resultsmentioning
confidence: 93%
“…Split applications of dimethyl 2,3,5,6-tetrachloro-1,4-benzenedicarboxylate (DCPA), N-butyl-N-ethyl-2,6-dinitro-4-(trifluoromethyl)benzenamine (benefin), or N-(2-methylcyclohexyl)-N´-phenylurea (siduron), or a single application of 6-chloro-N,N´-diethyl-1,3,5-triazine-2,4-diamine (simazine) or oxadiazon increased zoysiagrass plug coverage in the initial year of establishment. Conversely, when these same herbicides were used at a site where 'Meyer' sprigs were broadcast, no increase in coverage was noted in the first year (Fry et al, 1986). The latter results were attributed to higher zoysiagrass coverage within the nonherbicidetreated sprigged areas when compared to the site established with plugs.…”
Section: Methodsmentioning
confidence: 92%
“…The application of newer preemergence and postemergence herbicides (i.e., gramincides) to areas comprised of 'Meyer' zoysiagrass debris and sod ribbons, following sod harvest operations, suggests that these herbicides can hasten establishment from sprigs (Dernoeden and Carroll, 1992). However, preemergence herbicides can adversely affect rooting of zoysiagrass plugs (Fry et al, 1986). The effects of pre-and postemergence herbicides on the rooting of 'Meyer' zoysiagrass from sprigs has not been determined.…”
Section: Methodsmentioning
confidence: 99%
“…The preemergence herbicides oxadiazon and pendimethalin can increase stolon production and establishment rate of ‘Meyer’ zoysiagrass ( Z. japonica ) from plugs when annual grassy weeds are prevalent (Fry et al, 1986). Simazine is a commonly used preemergence herbicide in warm‐season turf production that does not negatively affect sod tensile strength or rooting of ‘Emerald’ zoysiagrass ( Z. japonica × Z. pacifica Goudsw.)…”
mentioning
confidence: 99%